Effect of feeding feed enzymes with phytogenic compounds on feed nutrient utilization in broiler chickens - Sze, E. K.; Loh, Tech Chwen (2011)
An efficient way of utilizing in-feed phytogenetic compound is by harnessing its nutritional effectsexerted on the animal’s digestive system. A blend of pyhtogenic substances (Biostrong®510) with standardized active ingredients that ensure consistent nutritional digestive effects was used to demonstrate synergism effect with feed xylanase-amylase in broiler diet. The effects of combinations of the phytogenic compounds and enzymes were shown by theirsignificant improvement in phosphorus (P) and calcium (Ca) digestibilities (P<0.05) by up to 51.5% and 59.0%. This treatment also improved gross energy (GE) digestibility of up to 29.8% (P<0.05). The synergism in nutrient digestibility can be explained by the differing digestive mode of action between phytogenic compounds and the enzymes in the broiler digestive tract.